Exploring Financial Resilience in Lampung Province: The Effect of Digital Financial Literacy, Numeracy Skills, and Financial Behavior on Youth - Haryati, Septi; Suripto, Suripto; Wardianto, Kussuyatmono Bagus; Pratama, Maulana Agung (The Es Accounting And Finance, 2024)
The unstable global economy, financial challenges, and limited research on financial preparedness in emergencies have made the topic of financial resilience a key topic among researchers, especially for generations Y and Z. This study examines the impact of digital financial literacy, numeracy skills, and financial behavior on financial resilience in Generation Y and Z in Lampung Province. This research is explanatory with a quantitative approach. Data analysis used multiple linear regression techniques. The sample was 100 Generation Y and Z in Lampung Province. The outcome of the examination revealed that partially, digital financial literacy and numeracy skills do not have a substantial effect on financial resilience. However, financial behavior has a substantial impact on financial resilience. Simultaneously, digital financial literacy, numeracy skills, and financial behavior have a significant effect on the financial resilience of Generation Y and Z in Lampung Province.